Hubungan Paparan Pb Dengan Gangguan Keseimbangan Tubuh Pada Pekerja Industri Peleburan Timah Hitam Di Kebasen Kabupaten Tegal - Leksono, Budi Bowo; Setiani, Onny; Sulistiyani, Sulistiyani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2014)
Background : Pb that enters the human body every day will be absorbed, stored and then accumulated in the blood. Health effects of exposure to lead include various influences cognitive function, learning ability, inhibit growth in height (stunting), hearing impairment, affecting behavior and intelligence, damaging the function of organs, such as kidneys, nervous system (one of which balance the body functions), reproduction, increases blood pressure and affect brain development. The purpose of this study was to determine the relationship between exposure to Pb with body balance disorders in workers in lead smelting industry Kebasen Tegal regency. Methods : A cross sectional study carried out on 39 workers at Village Small Industries Kebasen Tegal, Central Java. The variables used were Pb exposure with body balance disorders. The selection of the sample used simple random sampling technique as many as 39 workers. Relationship exposure Pb and body balance disturbances are analyzed using the chi square. Results : Result showed a total of 37 (94.9%) of respondents had blood lead levels > 10 mg/100 ml and the remaining 2 (5.1%) of the respondents had blood lead levels < 10 mg/100ml. A total of 27 (69,2%) of respondents impaired body balance and the remaining 12 (30,8%) of respondents not impaired body balance. There is a relationship between blood levels of Pb in the presence of body balance disorders. There is a relationship between the body of work with balance disorders. There is no relationship between the use of personal protective equipment by body balance disorders. There is no relationship between a history of social diseases with impaired body balance. Conclusion: There is a relationship between Pb exposure Pb with the body balance disorders. Keywords: Lead Exposure, Body Balance Disorders